ҚАРАҚАЛПАҚ ШАҢАРАҚЛАРЫН БЕККЕМЛЕЎДИҢ СОЦИАЛ ПСИХОЛОГИЯЛЫҚ ФАКТОРЛАРЫ - Темирбеков, Б.О. (FAN va JAMIYAT, 2023)
This article presents the factors of strengthening families by the example of the role of the Godfather, Godmother, who are assigned to young families, in ensuring the strength of the family.